2003
DOI: 10.1093/treephys/23.8.527
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet-B radiation alters phenolic salicylate and flavonoid composition of Populus trichocarpa leaves

Abstract: We investigated foliar phenolic composition of field- and greenhouse-grown Populus trichocarpa Torr. & A. Gray (black cottonwood) ramets subjected to near zero (0x), ambient (1x) or twice ambient (2x) concentrations of biologically effective ultraviolet-B (UV-B) radiation. After a 3-month treatment period, several age classes of foliage samples were harvested and the phenolic compounds extracted, separated by high performance liquid chromatography and identified and quantified by diode-array spectrometry and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 58 publications
2
61
2
1
Order By: Relevance
“…Thus, our results suggest that the stress tolerance of CsBGlu12 overexpression lines may be due to the accumulation of flavonols (kaempferol and quercetin), which are known to play key roles in abiotic stress (48). There are many instances where kaempferol and quercetin levels were shown to increase in response to UV-B irradiation (49). It has also been reported that a brief exposure of plants to UV-B provides a regulatory signal, eliciting the accumulation of flavonols to confer protection to UV-induced damage due to their absorption in this region (50,51).…”
Section: Analysis Of Gene Expression Has Often Been Useful To Gain Inmentioning
confidence: 66%
“…Thus, our results suggest that the stress tolerance of CsBGlu12 overexpression lines may be due to the accumulation of flavonols (kaempferol and quercetin), which are known to play key roles in abiotic stress (48). There are many instances where kaempferol and quercetin levels were shown to increase in response to UV-B irradiation (49). It has also been reported that a brief exposure of plants to UV-B provides a regulatory signal, eliciting the accumulation of flavonols to confer protection to UV-induced damage due to their absorption in this region (50,51).…”
Section: Analysis Of Gene Expression Has Often Been Useful To Gain Inmentioning
confidence: 66%
“…The activation of flavonol biosynthetic genes exhibited a reduction at 12 h, which may have been caused by the absence of the stimulus during the night or by circadian regulation. Flavonol glycosides are known to be important UV-B protective compounds (Li et al, 1993;Landry et al, 1995), and increased flavonol accumulation in leaves has been observed in poplar and other trees under elevated UV-B light (Warren et al, 2002(Warren et al, , 2003Keski-Saari et al, 2005;Turtola et al, 2005). HPLC analysis of extracts from leaves after 7 d of HL exposure revealed a large increase in total flavonol glycosides ( Fig.…”
Section: Identification Of Putative Pa Regulatory R2r3 Myb Genes In Pmentioning
confidence: 89%
“…Research to examine the species response to climate change would draw complementary data sets from observations and functional analyses, i.e., changed species interaction and chemical compositions. Global climate change conditions often alter plant chemical composition, which in turn can affect food and fodder quality and decomposition rates [2]. These alterations in the chemical composition of plants grown under the current climate can provide significant information concerning the impact of climate change on synthesis of secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%